Artificial Intelligence and Wage Justice in Indonesian Labour Law: Balancing Living Wage Standards and Corporate Capacity - Agusmidah; Titik Triwulan Tutik; Anna Maslova (PT. Islamic Research Publiser, 2026)
This article examines the implications of artificial intelligence (AI) in wage determination within Indonesian labour law, focusing on the tension between workers’ entitlement to a living wage and employers’ economic capacity. The study aims to analyse how AI-driven systems may reshape the concept of wage justice and to assess the adequacy of existing legal frameworks in responding to such technological developments. Employing a normative juridical method combined with conceptual and policy analysis, this research draws upon statutory regulations, legal doctrines, and comparative insights from international practices on algorithmic governance. The findings indicate that AI has the potential to enhance efficiency, consistency, and data-driven objectivity in wage-setting processes. However, its application also introduces significant challenges, including algorithmic bias, lack of transparency, and the risk of reinforcing distributive inequality. Indonesian labour law, which remains predominantly anchored in minimum wage mechanisms and macroeconomic indicators, is not yet equipped to regulate AI-based wage determination. As a result, integrating AI without a robust legal framework may undermine both substantive and procedural justice. This article argues that AI should be positioned as a supportive instrument rather than a decision-making authority in wage policies. It proposes a normative framework grounded in principles of transparency, accountability, human oversight, and fairness, while incorporating distributive justice theory and global standards on ethical AI governance. The study contributes to the advancement of labour law scholarship by offering a context-sensitive model for regulating AI in wage determination, particularly relevant for developing legal systems navigating the intersection of technological innovation and social justice.